2013
DOI: 10.1890/12-1237.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation legacies in desert grassland primary production occur through previous‐year tiller density

Abstract: In arid ecosystems, current-year precipitation often explains only a small proportion of annual aboveground net primary production (ANPP). We hypothesized that lags in the response of ecosystems to changes in water availability explain this low explanatory power, and that lags result from legacies from transitions from dry to wet years or the reverse. We explored five hypotheses regarding the magnitude of legacies, two possible mechanisms, and the differential effect of previous dry or wet years on the legacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
173
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(195 citation statements)
references
References 54 publications
14
173
4
1
Order By: Relevance
“…1). Results from the first 2 y, including a single transition for each treatment through years 2009 and 2010, agree with a previous experiment that showed that the negative effect of a previous-dry year on current-year ANPP was of the opposite sign but of the same magnitude as the positive effect of a previous-wet year on current-year ANPP (21). The effects of single dry-to-wet and wet-todry transitions cancelled each other and predicted null effects of interannual precipitation variation on average ANPP.…”
supporting
confidence: 88%
“…1). Results from the first 2 y, including a single transition for each treatment through years 2009 and 2010, agree with a previous experiment that showed that the negative effect of a previous-dry year on current-year ANPP was of the opposite sign but of the same magnitude as the positive effect of a previous-wet year on current-year ANPP (21). The effects of single dry-to-wet and wet-todry transitions cancelled each other and predicted null effects of interannual precipitation variation on average ANPP.…”
supporting
confidence: 88%
“…In order to predict the response of grassland ecosystems to future climate change, we need to understand the effects of environmental factors on the spatial and temporal changes of grassland biomass carbon stock. However, large uncertainties still exist on the amounts, spatial and temporal variability, and driving forces of grassland biomass, especially at the global scale [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Since shrub biomass accumulates over the course of several years, it shows a weak response to conditions of the present year (i.e., dry, normal, or wet) [23,46]. However, both a long-term (14 years) observational study [47] and a short-term (three years) rainfall manipulative experiment [48] also indicated that shrub ANPP showed low interannual variation and was only weakly dependent on annual precipitation. Poor response of shrub growth to precipitation could occur largely because the deep roots of these plants are able to utilize water from deep soil layers [49,50].…”
Section: Discussionmentioning
confidence: 99%